GEO-ECOLOGICAL ASSESSMENT TRANSFORMATION CONCENTRATION OF POLLUTANTS IN THE LOWER REACHES SYRDARIA WATERS - Mustafayev Ж.С.; Kozykeeva А.Т.; Abdiyvaliyeva К.С. (Hydrometeorology and ecology, 2023)
On the basis of ordering and system analysis of long-term information and analytical materials RSE «Kazhydromet» Pollution of water downstream of the Syr Darya evaluated water quality and environmental conditions that allow us to determine the intensity and direction of the transformation of pollutants in the space-time scale in terms of human activities.